2019
DOI: 10.1111/ijfs.14122
|View full text |Cite
|
Sign up to set email alerts
|

Purification and identification of kokumi‐enhancing peptides from chicken protein hydrolysate

Abstract: Summary The Maillard reaction products (MRPs) from chicken protein hydrolysate were demonstrated to have intense umami and kokumi‐enhancing effects. To find the main flavour‐enhancing compounds in the chicken protein hydrolysate, the fractions with different molecular weights were obtained by ultrafitration. The evaluation of taste characteristics revealed that the fractions with molecular weights ranging from 1000 to 5000 Da predominantly contributed to the umami and kokumi‐enhancing effects. After further pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Thus the MW < 1 kDa had strong umami taste which is in line with the previous studies (Alim et al, 2019;Kong et al, 2019). Other researchers also found that hydrolysates of different protein from plant sources and their MRPs could significantly enhance pleasant sensory characteristics (Zhang et al, 2019).…”
Section: Sensory Guided Fractionation By Ultrafiltration and Their Chemical Compositionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus the MW < 1 kDa had strong umami taste which is in line with the previous studies (Alim et al, 2019;Kong et al, 2019). Other researchers also found that hydrolysates of different protein from plant sources and their MRPs could significantly enhance pleasant sensory characteristics (Zhang et al, 2019).…”
Section: Sensory Guided Fractionation By Ultrafiltration and Their Chemical Compositionsupporting
confidence: 87%
“…Bitter, sweet and umami are the main tastes which are linked to the food rejection or acceptance (Baryłko-Pikielna & Kostyra, 2007).During processing of the extraction, protein degradation occurs and forms various amino acids and oligopeptide (Xua et al, 2021).Molecule responsible for taste such as kokumi-enhancing and umami peptide in yeast extract, beef broth, cheese and beans have been identified extensively in last two decades. Besides, in fermented corn sauce, a dipeptide comprising c-glutamyl have been recognized as the key kokumi compound (Zhang et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of oxalic acid (TC = 5,600 μM), tartaric acid, formic acid (TC = 4,345 μM), a C4:0, butyric acid; C6:0, caproic acid; C8:0, caprylic acid; C10:0, capric acid; C11:0, undecanoic acid; C12:0, lauric acid; C13:0, tridecanoic acid; C14:0, myristic acid; C15:0, pentadecanoic acid; C16:0, palmitic acid; C17:0, margaric acid; C18:0, stearic acid; C21:0, heneicosanoic acid; C22:0, behenic acid; C24:0, lignoceric acid; C14:1, myristoleic acid; C16:1, palmitoleic acid; C17:1, heptadecenoic acid; C18:1 n-9t, vaccenic acid; C18:1 n-9c, oleic acid; C18:2, linoleic acid; C18:3, α-linolenic acid; C20:1, eicosenoic acid; C20:2, eicosadienoic acid; C20:3, eicosatrienoic acid; C20:4, arachidonic acid; C20:5, timnodonic acid TA B L E 1 (Continued) pyroglutamic acid (TC = 9,798 μM), and fumaric acid were also determined in chicken/chicken soup (Horio & Kawamura, 1990;Norris et al, 1984;Stark et al, 2006;Zhang et al, 2020). Presently, the sour-tasting peptides reported in chicken or chicken soup include VE (TC = 8,121 μM), WVNEEDHL, NSLEGEFKG, and KDLFDPVIQD (Kong et al, 2017;Zhang, Ma, et al, 2019).…”
Section: Sweet-tasting Compoundsmentioning
confidence: 95%
“…The laws of a market economy place the cheese-making industry in a tough competition. In this situation, only scientifically grounded flexible assortment policy and high quality of products will help enterprises to take their rightful place in the cheese market [13][14][15].…”
Section: Introductionmentioning
confidence: 99%